POWER QUALITY IMPROVEMENT OF A 2.8kVA SINGLE PHASE GENERATOR USING A DOUBLE-TUNE FILTER (Nigerian Journal of Technology, 2019)
Improving power quality plays a vital role in power distribution systems. Nonlinear loads generate harmonics that disturbs power supply. This paper presents a control strategy in which data collected from a single phase generator (2.8 kVA) using ‘Owon’ oscilloscope. A double-tune filter configuration was developed to analyze the harmonic contents associated with the non-linear loads on the single phase generator.  MATLAB Simulation was carried on the data collected (voltage and frequency) from the power source using the double-tuned filter. It can be established from the frequency measured instead of the usual 50Hz on nameplate, the measured value was 46.160 Hz and the voltage values on Tables 1 and 2 that were transformed into waveforms and spectrum.  http://dx.doi.org/10.4314/njt.v38i2.21